Πρότυπη Γειτονιά – Πρότυπος Τόπος: Το προφίλ της γειτονιάς/του «τόπου» και περιθώριο βελτίωσης - Middleton, Nicos (My University, 2021)
The Place Standard tool (PST) provides a framework to structure conversations about Place in a holistic view but along a measurable set of dimensions. It was developed by NHS Scotland in partnership with the Scottish Government, Architecture and Design Scotland and Glasgow City Council. More than just a profiling tool, the PCT’s main goal is to prompt and encourage an inclusive dialogue among stakeholders in order to identify assets and recourses as well as challenges, pinpoint to areas for improvement and assist in setting priorities by consensus. Launched in 2015, it has since been used extensively in Scotland to engage with communities, develop a shared understanding of priorities and actions and shape collaborative decisions. Τhe tool can be used to assess different types and sizes of Places by individuals or groups. Available in multiple forms, including booklet, interactive and web version (www.placestandard.scot/), the tool allows flexibility. It can be used in print or digital form, in the context of surveys or focus groups, in formal settings or in walk-abouts. The PST contains a series of 14 items, each addressing a different dimension of Place, covering both physical as well as social aspects that can impact on health and well-being. Namely, these are: Moving Around, Public Transport, Traffic & Parking, Streets & Spaces, Natural space, Play & Recreation, Facilities & Amenities, Work & Local economy, Housing & Community, Social contact, Identity & Belonging, Feeling safe, Care & Maintenance, Influence & Sense of control. Permission to use the Place Standard was obtained by the developers. The tool was translated and adapted into Greek from the original English using a forward and backward translation process. The full booklet version, including the introductory information and instructions for completion, was translated into Greek by two of the authors independently of each other. After discussing and consolidating any discrepancies, a single Greek version was back-translated into English independently by the other two authors. Any issues were resolved by consensus with a focus on semantic equivalence. During the process, we were contacted by the Place Standard team with the request to collaborate with another team based in Cyprus (Cyprus Energy Agency) which had also used the Place Standard in the context of a Nicosia-based neighbourhood initiative. The two Greek translations were remarkably close and any small discrepancies were discussed and resolved through consensus between the teams. This resulted in the final version which was forwarded to the original team for future reference along with detailed explanations and justifications with regard to any adaptations deemed necessary, all of which were minor and did not result in any substantial differences from the original English version.
Place Standard: How good is our place? [Greek version]
Keywords: neighbourhood environment; assessment tool; place and health; community assessment